An Appalachian summer [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2020)
"In 1933, most people are focused on the Great Depression but all Piper Danson can think about is how to get out of being a debutante and marrying Braxton Crandall. In an act of defiance, Piper volunteers as a frontier nursing courier in the Appalachian Mountains where adventure awaits"--Provided by publisher.